SKRINING 9 JENIS TUMBUHAN ORDO SAPINDALES DI TAMAN HUTAN RAYA (TAHURA) SULTAN SYARIF HASYIM RIAU YANG BERPOTENSI SEBAGAI TUMBUHAN TERAPEUTIK - Simon Mangaratua; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Sultan Syarif Hasyim (SSH) Forest Park is one of the conservation areas in Riau Province. A total of 125 Spermatophyta species have been previously identified in thisregion. Those species are potencially used as therapeutic agens, especially Sapindales species. This study aimed to identify the Sapindales species from SSH forest park thathas therapeutic potencies based on their phytochemical test (alkaloids, flavonoids, steroids, terpenoids, saponins, and tannins). This study had been carried out fromNovember 2013 to February 2014. The sampling method used in this study was an exploration method. Data was descriptively analyzed. The result showed that total of nine Sapindales species from four families were identified. The number of species that positively contained alkaloids, flavonoids, steroids, terpenoids, saponins, and tannins were 7, 3, 6, 2,6 and 4, respectively.